Estudio de Amenazas y Vulnerabilidades en la Red de Comunicación del Departamento de Sistemas de la Universidad Técnica de Babahoyo - Chonana Sosa, Yordy Alejandro (2018)
Computer systems nowadays have become important elements in the development of society, of a country and of the world, establishing changes in the daily way of life of human beings, as well as of companies and organizations, that day Every day they strive to improve their services and reach places where they could not be reached. But to maintain these systems many important mechanisms arise which allow us to have those systems in an optimal state, in such a way that they can work correctly, reducing the information filtering rate, as well as cybernetic attackers. At the Technical University of Babahoyo, a drawback with the data network occurred some time ago (2 years ago), in which the main page of the university was affected, due to vulnerabilities that existed at that time; for this reason it is very important to detect problems in time to take the appropriate measures to solve or mitigate these problems, and thus provide a better service to both students and administrative staff of the UTB. In the present work, a scan was carried out using two well-known tools in terms of security, which are Nessus and Nmap of Kali Linux, in order to determine the vulnerabilities of the communication network, as well as the respective observations were made in regarding the result of said analysis. In addition, this work is included within the research lines of the Technical University of Babahoyo, specifically in the line of Development of Information Systems, Communication and entrepreneurial and technological enterprises, sub-line Process of Data Transmission and Telecommunications.